Feasibility Analyses of Integrated Broiler Production - M Firdaus; L Komalasari (Media Peternakan, 2010)
The major obstacles in the development of broiler raising is the expensive price of feed and the fluctuative price of DOCs. The cheap price of imported leg quarters reduces the competitiveness of the local broilers. Therefore, an effort to increase production efficiency is needed through integration between broiler raising and corn farmers and feed producers (integrated farming). The purpose of this study is to analyze the feasibility of integrating broiler raising with corn cultivation and feed production. Besides that, a simulation was conducted to analyze the effects of DOC price changes, broiler price and production capacity. The analyses showed that integrated farming and a mere combination between broiler raising and feed factory of a 10,000 bird capacity is not financially feasible. Increasing the production to 25,000 broiler chickens will make the integrated farming financially feasible. Unintegrated broiler raising is relatively sensitive to broiler price decreases and DOC price increases compared to integrated farming.